The law of large numbers and finite variety in death-related dreams - Paquette, Andrew (Journal of Scientific Exploration, 2015)
Leave-taking dreams contain a message to the dreamer that a person has died. If the dream is roughly simultaneous with the death of the person featured in the dream, they can be described as veridical. Critics of leave-taking dream accounts dismiss them as the product of the random alignment of single dreams from unrecorded large series of similar dreams. This criticism is possible because examples tend to be isolated among the written artefacts available to researchers. That is, complete dream histories are rare. Without a complete dream history it is not possible to ascertain how common death dreams are for any given person, or how frequently specific people are featured in such dreams. Is it possible that veridical leave-taking dreams are simply the chance product of one of a long series of similar dreams eventually matching the date of an individual’s death? To address this question, this paper makes a retrospective analysis of the author’s own dream journals, which cover a near continuous span of over twenty-four years. This analysis suggests that the Law of Large Numbers is an inadequate means of nullifying arguments in favour of the existence of veridical leave-taking dreams.